2008
DOI: 10.1111/j.1600-6143.2007.02058.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Transplantation Followed by Auxiliary Liver Transplantation—a Novel Treatment for Ornithine Transcarbamylase Deficiency

Abstract: † These authors contributed equally to this work.We report the first successful use of hepatocyte transplantation as a bridge to subsequent auxiliary partial orthotopic liver transplantation (APOLT) in a child antenatally diagnosed with severe ornithine transcarbamylase (OTC) deficiency. A total of 1.74 × 10 9 fresh and cryopreserved hepatocytes were administered intraportally into the liver over a period of 6 months. Immunosuppression was with tacrolimus and prednisolone. A sustained decrease in ammonia level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 20 publications
1
67
0
2
Order By: Relevance
“…En la serie más extensa hallada la supervivencia fue del 91%, la hiperamoniemia y la dieta restrictiva fueron erradicadas en estos pacientes 14 . Actualmente también se valora la posibilidad de realizar transplante de hepatocitos como puente a un transplante ortotópico parcial hepático 15 .…”
Section: Discussionunclassified
“…En la serie más extensa hallada la supervivencia fue del 91%, la hiperamoniemia y la dieta restrictiva fueron erradicadas en estos pacientes 14 . Actualmente también se valora la posibilidad de realizar transplante de hepatocitos como puente a un transplante ortotópico parcial hepático 15 .…”
Section: Discussionunclassified
“…Thus, cell maturity may prove to be critical for diseases requiring functional differentiated cells. In some instances of end-stage liver disease, and for inborn errors of liver metabolism, an entire liver may not be required and auxiliary partial liver transplantation has been suggested as a therapeutic option, 243 although a graft representing at least 35% of a liver would be necessary.…”
Section: Clinical Innovation In Transplantationmentioning
confidence: 99%
“…[kg]) has been demonstrated in human clinical trials [7], it has been reported that replacement of at least 10% of the hepatocellular mass is needed to compensate for missing or inactive proteins in genetic inborn errors of metabolism [8].…”
Section: Primary Hepatocytesmentioning
confidence: 99%